(untitled) (Journal of Medicine, 2026)
Objectives: To examine the demographics, disease severity, hospital stay duration, intensive care unit (ICU) stay, and per-patient cost (PPC) of melioidosis cases in Eastern and Northern Malaysia. Methods: A total of 502 patients in six hospitals in Eastern and Northern Malaysia were included in the study. Descriptive statistics were used to analyze patient demographics, disease severity, comorbidities, length of stay (LOS), and ICU stay. One-way ANOVA and Kruskal-Wallis tests were applied to compare LOS and ICU stay based on comorbidities. Pearson chi-square test was used to identify the association between comorbidities and severity. Results: LOS and ICU duration were significantly influenced by comorbidity burden (P<0.001). Patients with three or more comorbidities had the longest LOS (mean±SD = 38.0±39.4 days) and ICU stays (median±IQR = 1.0±19.0 day) compared to those without comorbidities (LOS mean±SD = 17.9±17.8 days; ICU median±IQR = 0.0±0.00 day). Hospitals’ PPC for melioidosis differed from 2017 to 2020. Costs varied at Hospital Sultanah Nur Zahirah but increased dramatically at Hospital Raja Perempuan Zainab II. Conclusions: Melioidosis remains a severe disease with a substantial healthcare burden, especially among patients with multiple comorbidities. Disease severity, sex, and comorbidity count significantly affect hospital and ICU stay durations.The findings highlight the need for early risk identification and targeted resource allocation to improve patient outcomes and manage hospital costs effectively. J MEDICINE 2026; 27(1): 27-34